Sexual Online Grooming of Children: Challenges for Science and Practice (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
Preparing potential victims for their later sexual abuse has always been an integral part of child sexual victimization. Sexual grooming is thus a common epiphenomenon of child sexual abuse that has already been described for child sexual abusers in the pre-internet era. With the advent of the Internet, online sexual grooming (SOG) of children has sparked new interest in this topic. This book provides a comprehensive description of the phenomenon of online sexual grooming (SOG) of children. In addition to a description of the content of SOG, characteristics of victims and perpetrators as well as possibilities for prevention and prosecution and implications for science and practice are presented.